Simulasi dan Analisa Performansi Buck Converter Dengan Pengendali Dua Derajat Kebebasan - Heru Dibyo Laksono; Firmansyah Saputra; Ismail Ismail (JURNAL NASIONAL TEKNIK ELEKTRO, 2018)
DC power supply are commonly used to convert DC voltage level to another level. One type of DC power supply is a buck converter that is used to lower a voltage level. In order to have a proper feedback of voltage output in buck converter system, it will be controlled by a  Two Degrees of Freedom PID Controller. This research aim to analyze the performance of the buck converter that have a Two Degrees of Freedom PID Controller. Two Degrees of Freedom Controller has proportional, integral and derivative control parameters. The simulation of the system is made with the help of software MATLAB. The first simulation and analysis is buck converter system without controller. From the analysis, the desired criteria is obtained . Then a buck converter system was designed. It is controlled using a parallel type of Two Degrees of Freedom PID Controller as well as feedforward, feedback, and filter. From all these types of controllers, it showed that the first order of Proportional Differential Filter (PDF) feedforward type with the value of  Kp = 171, Kd = 0.00545, Tf = 4.88e-07 and the first order of  PDF feedback type with the value of Kp = 171, Kd = 0.00545, Tf = 4.88e-07 was considered as the proper controller that matched with the characteristic. Therefore, it could be concluded that the buck converter controlling system with Two Degrees of Freedom PID Controller could produce a buck converter system with a good performance compared to buck converter without any controllers.Keywords:   Buck converter, Two Degrees of Freedom PID Controller, control system, time domain performance.